The Role of the Iraq Stock Exchange in Creating Government Fiscal Space: A Forward-looking Perspective - Inaam Majeed Abdul Hussein; Ali Hussein, Safaa (Journal of Economics and Administrative Sciences, 2024)
The stock market is one cornerstone of an economy, and relying on limited financial resources in any country has become increasingly challenging. Recognizing the significance of the financial market in bridging the financing gap in the economy, most countries have acknowledged its pivotal role, especially in the aftermath of numerous global financial crises. This acknowledgement involves mobilizing savings from surplus entities to deficit entities and channeling them into various investments by issuing financial instruments such as stocks, bonds, and government securities. Consequently, the financial market provides liquidity and cash flow, creating a fiscal space that can be utilized to fund developmental investment projects without the need for external borrowing and the associated risks of high interest rates on loans, which can impact the government’s ability to repay. Therefore, the primary objective of this study is to analyze the reality of the Iraqi securities market (ISX) using financial market indicators and the government’s ability to leverage the financial market to generate high financial, which Iraq’s government needs. Thereby expanding the government’s Fiscal space. The research revealed that the Iraqi securities market (ISX) needs more capacity to diversify its financial sources and attract local and international investments. Additionally, there is an almost complete absence of the issuance of government securities, which could contribute to creating the government’s Fiscal space. Paper: Research paper